2011
DOI: 10.1016/j.jaci.2010.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Human TH17 cells express a functional IL-13 receptor and IL-13 attenuates IL-17A production

Abstract: Background IL-13 is a central mediator of airway responsiveness and mucus expression in allergic airway inflammation and IL-13 is currently a therapeutic target for asthma. However, little is known about how IL-13 regulates human CD4+ T cell lineages because the IL-13 receptor α1 (IL-13Rα1), a subunit of the IL-13 receptor, has not previously been reported to exist on human T cells. Objective To determine if human CD4+ Th17 cells express IL-13Rα1 and if IL-13 regulates Th17 cytokine production. Methods Naï… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 33 publications
7
75
1
Order By: Relevance
“…GLPG0634 efficiently blocks cytokine-induced signaling cascades involving JAK1 in several cell lines as well as in human primary cells. Moreover, Th1, Th2, and Th17 differentiation driven by cytokine cocktails, including JAK1-dependent cytokines such as IL-2, IL-4, and IL-6, is also inhibited by GLPG0634 (17,18). These in vitro findings translate to pharmacodynamic readouts in rodents showing that JAK1 signaling is blocked in vivo as measured by a reduction of Mx2 mRNA levels.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…GLPG0634 efficiently blocks cytokine-induced signaling cascades involving JAK1 in several cell lines as well as in human primary cells. Moreover, Th1, Th2, and Th17 differentiation driven by cytokine cocktails, including JAK1-dependent cytokines such as IL-2, IL-4, and IL-6, is also inhibited by GLPG0634 (17,18). These in vitro findings translate to pharmacodynamic readouts in rodents showing that JAK1 signaling is blocked in vivo as measured by a reduction of Mx2 mRNA levels.…”
Section: Discussionmentioning
confidence: 80%
“…Isolated naive CD4 + T cells were stimulated with plate-bound anti-CD3 (3 mg/ml) and anti-CD28 (5 mg/ml) Abs in the presence of cytokines that drive differentiation into Th1, Th2, or Th17 Th subsets. For Th1 cell polarization, cells were cultured in the presence of 10 mg/ml anti-IL-4 Ab (MAB204; R&D Systems), 10 ng/ml IL-2 (R&D Systems), and 10 ng/ml IL-12 (R&D Systems) (17). For Th2 cell polarization, cells were cultured in the presence of 10 mg/ml anti-IFN-g Ab (Becton Dickinson), 25 ng/ml IL-4 (R&D Systems), and 10 ng/ml IL-2 (17).…”
Section: Cellular Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of the complex interaction of interleukins was provided by Newcomb et al 3 They observed that IL-13 downregulated murine TH17 T cell differentiation and showed that human TH17 T cells expressed IL-13α1, which mediated inhibition of IL17A production. The authors suggested that strategies targeting IL-13 effects for asthma and allergic diseases might increase TH17 responses.…”
Section: Cytokinesmentioning
confidence: 99%
“…It is through this Type II receptor complex that IL-4 and IL-13 mediate their effects on non-hematopoietic cells, which generally lack C, and therefore Type I receptor expression. IL-13R1 surface expression is absent on resting mouse and human T-cells and on mouse B-cells (Ogata, et al, 1998, Umeshita-Suyama, et al, 2000, although recent studies suggested inducible expression on mouse and human CD4+ T-cells (Newcomb, et al, 2009, Newcomb, et al, 2011. Related evolutionarily to C, IL-13R1 has acquired a third extra Ig-like domain, D1, allowing extra contacts with IL-13 in Type II receptor complexes (LaPorte, et al, 2008).…”
Section: Il-13 Receptor 1 (Il-13r1)mentioning
confidence: 99%